Promoting restorative practices and child friendly justice for children in conflict with the law: the Kenyan context - Gakuo, Isabel Wanjiru (Strathmore University, 2018)
The core objective of this study is to propose the adoption of restorative justice as a complementary mechanism of dealing with juvenile offenders in Kenya. This paper hypothesizes that high rates of recidivism and juvenile crime in Kenya is primarily attributed to the retributive nature of the juvenile justice system. It recognizes that more often than not, the current system fails to meet the primary objectives of efficient child justice which is to rehabilitate offenders, deter them from future criminal behaviour, reintegrate them into the society and restore social harmony with all stakeholders. This research therefore encompasses an analytical study of restorative justice in different countries where it has been adopted as best practice for juveniles. This is done by looking at international, regional and national legal frameworks and principles that support restorative practices. This paper also demonstrates the rates of success of restorative justice in combating juvenile crime compared to instances where it was not applied. The research methodology is purely qualitative, relying on reports of previous studies and relevant academic writing on this area. The study concludes with findings that restorative justice has not expressly been considered or implemented in the Kenyan juvenile system however prevailing legislation as well as existing Traditional Dispute Resolution Mechanisms set the stage for possible adoption of restorative measures involving communities and the civil society in dealing with children in conflict with the law. The paper recommends that there should be increased implementation of restorative measures which Kenyan laws already provide for, whilst progressively incorporating those that have been seen to work in other jurisdictions.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Juvenile Offenders; Recidivism; Juvenile Crime; Juvenile Justice System; Dispute Resolution Mechanisms